A novel finding of oligodontia and ankyloglossia in a 14‐year‐old with Floating‐Harbor syndrome. (6th December 2017) - Singh, Akshara; Bhatia, Hind Pal; Sood, Shveta; Sharma, Naresh; Mohan, Amit
ABSTRACT: Floating‐Harbor syndrome (FHS) is a rare genetic condition characterized by distinct facial features, short stature and delayed skeletal development. Here we present case of a 14‐year‐old boy with short stature, typical facial features, impaired voice quality, clinodactyly, cryptorchidism and unilateral agenesis of kidney. In addition he had oligodontia and ankyloglossia with features suggestive of FHS. Treatment rendered was restoration of caries, application of pit and fissure sealants followed by frenectomy. The purpose of this report is to highlight the oral developmental anomalies and the management of a patient with FHS and to add to the current knowledge of the literature on this syndrome.